Back Cover: Monodispersed CuCo Nanoparticles Supported on Diamine‐Functionalized Graphene as a Non‐noble Metal Catalyst for Hydrolytic Dehydrogenation of Ammonia Borane (ChemNanoMat 10/2016). Issue 10 (27th September 2016) - Song, Fu‐Zhan; Zhu, Qi‐Long; Yang, Xin‐Chun; Xu, Qiang
Abstract : Monodispersed non‐noble CuCo nanoparticles (NPs) have been immobilized on diamine‐functionalized reduced graphene oxide (rGO). The resulting material exhibits excellent catalytic activity for the hydrolytic dehydrogenation of ammonia borane. More information can be found in the Communication by Q. Xu et al. onpage 942 in Issue 10, 2016 (DOI:10.1002/cnma.201600198 ).